1996
DOI: 10.1016/0014-5793(96)00027-0
|View full text |Cite
|
Sign up to set email alerts
|

UV‐B‐ and oxidative stress‐induced increase in nicotinamide and trigonelline and inhibition of defensive metabolism induction by poly(ADP‐ribose)polymerase inhibitor in plant tissue

Abstract: Nicotinamide and trigoneUine contents increased in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 42 publications
6
42
1
Order By: Relevance
“…PARP inhibitor studies have demonstrated the involvement of PARPs in abiotic stress (Amor et al, 1998;De Block et al, 2005) and defense responses (Berglund et al, 1996;Adams-Phillips et al, 2008). A role for PARP activity in seeds to protect against genotoxic stress has also been inferred (Hunt and Gray, 2009).…”
mentioning
confidence: 99%
“…PARP inhibitor studies have demonstrated the involvement of PARPs in abiotic stress (Amor et al, 1998;De Block et al, 2005) and defense responses (Berglund et al, 1996;Adams-Phillips et al, 2008). A role for PARP activity in seeds to protect against genotoxic stress has also been inferred (Hunt and Gray, 2009).…”
mentioning
confidence: 99%
“…Determination of nicotinamide and trigonelline coneentrations. The plant material ("1 g) was weighed, triturated with sand, extracted and quantified according to Berglund et al (1996). To be able to directly compare the different results in this report, be it from nicotinamide, trigonelline, GSH or transcript level determinations, and to avoid diurnal variations, the results were all expressed as percentage of the initial control sample of each measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was conducted in order to further elucidate the effect of UV-B radiation, low and high doses, on the accumulation of nicotinamide and trigonelline in plant tissue, which was shown in Berglund et al (1996) and on the level of oxidative processes (manifested as changes in GSWGSSG) and mRNA levels of defence-related and other proteins. Especially we wanted to investigate any relationship between UV-B-induced changes in nicotinamide or trigonelline levels and the expression of defence genes in connection with oxidative stress.…”
mentioning
confidence: 99%
“…Despite the old5 mutation, pyridine nucleotide levels in the mutant were increased compared with the wild type. This might be due to the activation of a stress response program, since increased expression of the NAD salvage pathway is reminiscent of the need to replenish the NAD pool during stress conditions (Berglund et al, 1996;Hunt et al, 2007;Wang and Pichersky, 2007). One example of a NAD-consuming enzyme induced by oxidative stress is poly(ADP-ribose) polymerase (De Block et al, 2005), linking increased salvage metabolism to stress.…”
Section: Pyridine Biosynthesis Crosstalk and Stress Programming In mentioning
confidence: 99%